Crossing the Line: The Experiences of First-Generation Emirati Female Students. Issue 2 (4th May 2022) - Mahani, Sepideh
ABSTRACT: A majority of the current students enrolled in the United Arab Emirates' federal colleges and universities are first-generation students. Although the number of first-generation students is high, there is a lack of information on the experiences of these students. The lack of information on the academic, social, and familial experiences of the Emirati female first-generation students stymies governmental and educational initiatives to address the special needs of these students. For that reason, investigating the problem could help identify programs and resources that can assist first-generation students meet their academic aspirations. The purpose of this qualitative case study was to gain an understanding of the academic, social, and familial experiences of first-generation Emirati students in a higher education institution in the United Arab Emirates. Six female first-generation Emirati Bachelor students from the Higher Colleges of Technology participated in open-ended, in-depth, semi-structured interviews to discuss their academic, social and familial experiences. A series of in-depth and follow-up interviews were conducted until data saturation was reached.